2015
DOI: 10.1021/jp509694h
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Structures of the Gas-Phase Hydrated Cations M+(H2O)nAr (M = Li, Na, K, Rb, and Cs;n= 3–5) Using Infrared Photodissociation Spectroscopy and Thermodynamic Analysis

Abstract: The hydration of alkali cations yields a variety of structural conformers with varying numbers of water molecules in the first solvation shell. How these ions move from the aqueous phase into biological systems, such as at the entrance of an ion channel, depends on the interplay between competing intermolecular forces, which first must involve ion-water and water-water interactions. New infrared action spectra, using argon as a messenger or "spy", for Li(+), Na(+), and K(+), with up to five water molecules are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 119 publications
7
34
0
Order By: Relevance
“…First, the number of distinguishable bands is related to the heterogeneity of H-bonding environments of water molecules at the surfaces of these clusters. The frequencies of free OH stretches are exquisitely sensitive to a water molecule's H-bonding environment, 62 68 , 79 , 88 , 89 and the free OH stretch of a water molecule red-shifts as the water molecule's participation in H-bonding increases. Using the nomenclature where “A” denotes a H-bond accepted by a water molecule and “D” denotes a H-bond donated by a water molecule, free OH bands appear in increasing frequency following the order AAD < AD ≈ AA < A.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the number of distinguishable bands is related to the heterogeneity of H-bonding environments of water molecules at the surfaces of these clusters. The frequencies of free OH stretches are exquisitely sensitive to a water molecule's H-bonding environment, 62 68 , 79 , 88 , 89 and the free OH stretch of a water molecule red-shifts as the water molecule's participation in H-bonding increases. Using the nomenclature where “A” denotes a H-bond accepted by a water molecule and “D” denotes a H-bond donated by a water molecule, free OH bands appear in increasing frequency following the order AAD < AD ≈ AA < A.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of a single ion or electron on water structure can be investigated as a function of hydration extent, ranging from a single water molecule up to hundreds of water molecules, and information about ion solvation can be obtained in the limit of infinite dilution. 55 61 Infrared photodissociation (IRPD) spectroscopy can probe the structures of numerous gas-phase hydrates, including metal ions, 62 68 anions 26 , 28 , 69 72 and protonated/ionized amino acids and peptides. 73 76 Heteroatom-hydrogen stretching frequencies are sensitive to their local H-bonding environment, and IRPD measurements have been used to elucidate detailed hydration structures of ions with up to ∼20 water molecules attached.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, some of the structures of the Na + (H 2 O) n ( n = 1–6) clusters are adopted from previous literatures (Bauschlicher et al, 1991; Glendening and Feller, 1995; Ke et al, 2015; Fifen and Agmon, 2016). To obtain more isomers for n = 4–6, a global search with the comprehensive genetic algorithm (CGA, Zhao et al, 2016) combined with DMol 3 program (Delley, 2000) based on DFT was executed.…”
Section: Methodsmentioning
confidence: 99%
“…The infrared (IR) spectra are available in distinguishing the cluster isomers. For hydrated sodium ion clusters, the feature peaks of O–H stretching mode could accurately provide the structure information of clusters (Huang and Miller, 1989; Patwari and Lisy, 2003; Vaden et al, 2004; Miller and Lisy, 2008a,b; Ke et al, 2015), in which the non-covalent interactions, including ion–water interaction and hydrogen bond, weaken the O–H bonds, causing redshifts for O–H stretching vibration modes and producing different feature peaks for different structures (Muller-Dethlefs and Hobza, 2000; Vaden et al, 2002, 2004, 2006; Kozmutza et al, 2003; Bush et al, 2008; Miller and Lisy, 2008a), Using a custom-built, triple-quadrupole mass spectrometer as well as ab initio calculations, Lisy et al reported the IR spectra of Na + (H 2 O) n ( n = 2–5) and Na + (H 2 O) n Ar ( n = 2–5) (Miller and Lisy, 2008a,b; Ke et al, 2015). For n = 4, 3+1+0 is the stable structure with bent hydrogen bonds (Miller and Lisy, 2008a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation